(untitled) (Nepalese Journal of Management Research, 2024)
This article explores the complex realm of gastronomical tourism through an examination of a traditional dish called “Taas,” or grilled mutton chunk, and how it influences visitors’ opinions of Chitwan, Nepal. The culinary appeal of Taas is still an underappreciated aspect of Chitwan’s attractiveness, despite its lush surroundings, abundant species, rich biodiversity and cultural legacy. The goal of this research is to identify the complex relationships that exist between flavour, cultural authenticity, and overall tourist satisfaction. Through an analysis of the sensory sensations linked to Taas eating, the study sheds light on the nuanced but significant connections between cuisine, cultural identity, historical preservation, and tourism economics. The study’s conclusions have practical ramifications for nearby companies, decision-makers, and tourism stakeholders in addition to enhancing the academic conversation on culinary tourism. Gaining insight into how Taas shapes visitors’ opinions is essential for strategically promoting Chitwan’s culinary legacy. It also promotes a greater understanding of the complex interrelationships that exist between food, culture, and tourism, highlighting the necessity of sustainable measures that protect culinary customs while improving the general guest experience.